Histochemical Study of the Progenetic Trematode Alloglossidium renale - Craig A. Schimmer; Stephen C. Landers (Journal of Parasitology Research)
A histochemical study of the progenetic trematode Alloglossidium renale has demonstrated the absence of any secreted material between the adult worm and the host (freshwater shrimp) antennal gland tubules. Host tissue is affected only by the compression, abrasion, and ingestion by the parasite, and host tubule cells near the worm have the same staining patterns as those distant from the parasite. The trematode sometimes dies within the host, leaving a necrotic mass whose histochemical staining differs significantly from the living organism. In the necrotic mass, the only recognizable features were the ova and the vitellarium, which atrophied and resulted in tyrosine-positive staining within the mass. A melanin reaction was not observed in the host using a specialized ferro-ferricyanide stain. The only apparent host response to infection was a layer of damaged squamous host cells adhering to the necrotic worm. The results confirm benign host-parasite effects and a highly evolved relationship between the host and parasite, perhaps bordering on commensalism.